Bridging Cultural Capital and Academic Achievement: The Study of Rana Tharu Community - Pandey, Om Prakash (Journal of Indigenous Knowledge and Practice, 2025)
This study aims to examine how Rana Tharu students use their cultural resources to navigate academic challenges, incorporating Pierre Bourdieu’s theory of cultural capital. The primary objective of this study is to explore the cultural capital and academic pursuits of the Rana Tharu community, given the limited empirical evidence available to conclusively determine the factors contributing to their educational marginalization in relation to their cultural capital. Furthermore, it identifies the real challenges faced by Rana Tharu pupils due to inadequacies in educational institution, so that corrective measures can be implemented to raise their academic achievement. Following ethnographic critical lens as a research design, it aims to investigate whether or not current social policies and practices are meeting the interests of a certain group. The study is especially concerned with examining how the current educational system falls short of meeting the requirements of minority groups, such as the Rana Tharus to integrate them into the mainstream of education. The findings of the study reported that Rana Tharu students have their own cultural and ethnic identities, and different cultural capitals. However, our mainstream schools are not found to be much friendly to minorities. Although it is claimed that mainstream schools are for all ethnicities, they mostly favor the culture of the dominant ethnic group.